2016
DOI: 10.1080/19390211.2016.1207004
|View full text |Cite
|
Sign up to set email alerts
|

Critical Review on Eliminating Endodontic Dental Infections Using Herbal Products

Abstract: The main purpose of a root canal treatment is to eliminate the bacteria and their products from the pulp space. Chemomechanical preparation (chemical-refers to irrigating solutions, i.e., either synthetic chemicals or herbal solutions and mechanical-refers to instrumentation of a root canals with endodontic files) of a root canal system plays a major role in obtaining the rationale of root canal treatment. Various synthetic chemicals known as endodontic irrigants play a major role in disinfection, but also hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…In addition, another group reported that Triphala in 10% DMSO was more effective than 5.25% NaOCl solution against E. faecalis biofilms on ex vivo tooth substrate and suggested the extract as an alternative in the context of clinical root canal irrigation. 40 , 41 A study using human primary teeth ex vivo revealed that Triphala suspended in 10% DMSO (1:3) exhibited significant antibacterial activity compared with control as well as higher antibacterial activity compared with 3% NaOCl. 42 In vitro studies using Triphala ethanol extract have reported similar antimicrobial effects against E. faecalis compared with 2.5% NaOCl.…”
Section: Therapeutic Uses and Studiesmentioning
confidence: 99%
“…In addition, another group reported that Triphala in 10% DMSO was more effective than 5.25% NaOCl solution against E. faecalis biofilms on ex vivo tooth substrate and suggested the extract as an alternative in the context of clinical root canal irrigation. 40 , 41 A study using human primary teeth ex vivo revealed that Triphala suspended in 10% DMSO (1:3) exhibited significant antibacterial activity compared with control as well as higher antibacterial activity compared with 3% NaOCl. 42 In vitro studies using Triphala ethanol extract have reported similar antimicrobial effects against E. faecalis compared with 2.5% NaOCl.…”
Section: Therapeutic Uses and Studiesmentioning
confidence: 99%
“…The dried powders A. arabica (bark), T. Chebula (fruits), T. bellerica (fruits) and E. officinalis (fruits) plants have been used in traditional tooth powder formulation in India for more than 100 years (unpublished). Already many reports are available for the validation of numerous of potential benefits of these four plant material including anti-cariogenic properties [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] and these plant materials possess abundance of bioactive compound like quercetin, luteolin, saponins, anthraquinones, amino acids, fatty acids, various carbohydrates and polyphenols such as chebulinic acid which can exhibit the antimicrobial activities [34] , [35] . The above four plant materials used in this study having the potential to protect users against oral diseases, but this potential and the possible mechanism has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Its actual mode of action in these cases needs to be evaluated more and patients need to be put on a follow-up to see results. [ 44 45 ]…”
Section: Discussionmentioning
confidence: 99%